2021
DOI: 10.3390/socsci10110446
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Financialization of the Criminal Justice System

Abstract: (1) The increase in women’s mass incarceration over the past forty years raises questions about how justice-involved women experience the financial aspects of the criminal justice system. (2) We conducted in-depth interviews with twenty justice-involved women and seven criminal law and reentry professionals, and conducted courtroom observations in southeastern Pennsylvania. (3) The results from this exploratory research reveal that women’s roles as caregivers, their greater health needs, and higher likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A study examining the effects of criminal stigma concluded that employment affects the reduction of crimes committed by male and that financial pressure has a positive effect on the increase in female criminal behavior 24 . The financial costs of involvement in the criminal justice system, such as fees and fines, further increase the economic instability of women upon reentry, and making it difficult for them to reintegrate into society 25 . In India, socio-economic factors, including financial coercion, maladjustment of relationships and personality traits, have been as important drivers of women's crimainal behavior 26 .…”
Section: Factors Affecting Women's Criminality Socioeconomic Factors -mentioning
confidence: 99%
“…A study examining the effects of criminal stigma concluded that employment affects the reduction of crimes committed by male and that financial pressure has a positive effect on the increase in female criminal behavior 24 . The financial costs of involvement in the criminal justice system, such as fees and fines, further increase the economic instability of women upon reentry, and making it difficult for them to reintegrate into society 25 . In India, socio-economic factors, including financial coercion, maladjustment of relationships and personality traits, have been as important drivers of women's crimainal behavior 26 .…”
Section: Factors Affecting Women's Criminality Socioeconomic Factors -mentioning
confidence: 99%
“…Just as individuals face disparate treatment when it comes to the enforcement of LFOs by police and court officials, different groups of people face different severities of consequences. A critical area of emerging research shows LFOs may be higher, more punitive, and result in more negative outcomes for certain groups, such as people who are Black or African American (Bing et al., 2022; Link, 2019), people with precarious immigration statuses (Sanchez et al., 2022), Native Americans (Stewart et al., 2022), women (O’Neill et al., 2022; Servon et al., 2021), and those living in poverty (Bing et al., 2022; Rafael & Mai, 2022; Slavinski & Spencer‐Suarez, 2021; Ward & Link, 2022). Taking an intersectional approach, studies demonstrate how some people face several factors at once that multiply the harm of legal debt.…”
Section: Consequencesmentioning
confidence: 99%